A Novel Control Technique for Voltage Balancing in Bipolar DC Microgrids - Hajar Doubabi (Energies, 2022)
The bipolar DC microgrid topology is characterized by three voltage levels and is able to transfer power more efficiently than a conventional DC microgrid. This paper proposes an advanced control strategy aiming to ensure the voltage balancing between the upper and lower terminals of a bipolar DC microgrid regardless of the distribution of loads. The proposed controller is based on the backstepping method, which is well known for its the robustness and the global asymptotic stability that can be guaranteed for the system. A particle swarm optimization algorithm has also been adopted for an optimal design of the proposed controller parameters. Simulation results in a Matlab/Simulink environment has been presented to verify the effectiveness and reliability of the proposed voltage-balancing controller.